Cybersecurity public sector threats and responses - Andreasson, Kim J. (Public administration and public policy, 2012)
The Internet has given rise to new opportunities for the public sector to improve efficiency and better serve constituents in the form of e-government. But with a rapidly growing user base globally and an increasing reliance on the Internet, digital tools are also exposing the public sector to new risks. An accessible primer, Cybersecurity: Public Sector Threats and Responses focuses on the convergence of globalization, connectivity, and the migration of public sector functions online. It identifies the challenges you need to be aware of and examines emerging trends and strategies from around the world. Offering practical guidance for addressing contemporary risks, the book is organized into three sections: